Simple Estimates for Local Prevalence of Latent Tuberculosis Infection, United States, 2011–2015 - Haddad, Maryam B. (Emerg Infect Dis, 2018)
We used tuberculosis genotyping results to derive estimates of prevalence of latent tuberculosis infection in the United States. We estimated <1% prevalence in 1,981 US counties, 1%–<3% in 785 counties, and >3% in 377 counties. This method for estimating prevalence could be applied in any jurisdiction with an established tuberculosis surveillance system.